Anti-Inflammatory Effects of Ellagic Acid on Acute Lung Injury Induced by Acid in Mice - Daniely Cornélio Favarin; Maxelle Martins Teixeira; Ednéia Lemos de Andrade; Claudiney de Freitas Alves; Javier Emilio Lazo Chica; Carlos Artério Sorgi; Lúcia Helena Faccioli; Alexandre Paula Rogerio (Mediators of Inflammation)
Acute lung injury (ALI) is characterized by alveolar edema and uncontrolled neutrophil migration to the lung, and no specific therapy is still available. Ellagic acid, a compound present in several fruits and medicinal plants, has shown anti-inflammatory activity in several experimental disease models. We used the nonlethal acid aspiration model of ALI in mice to determine whether preventive or therapeutic administration of ellagic acid (10 mg/kg; oral route) could interfere with the development or establishment of ALI inflammation. Dexamethasone (1 mg/kg; subcutaneous route) was used as a positive control. In both preventive and therapeutic treatments, ellagic acid reduced the vascular permeability changes and neutrophil recruitment to the bronchoalveolar lavage fluid (BALF) and to lung compared to the vehicle. In addition, the ellagic acid accelerated the resolution for lung neutrophilia. Moreover, ellagic acid reduced the COX-2-induced exacerbation of inflammation. These results were similar to the dexamethasone. However, while the anti-inflammatory effects of dexamethasone treatment were due to the reduced activation of NF-κB and AP-1, the ellagic acid treatment led to reduced BALF levels of IL-6 and increased levels of IL-10. In addition, dexamethasone treatment reduced IL-1β. Together, these findings identify ellagic acid as a potential therapeutic agent for ALI-associated inflammation.